2006
DOI: 10.2458/azu_jrm_v59i2_moore
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous Vegetation Responses (1992-2004) to Restoration Treatments in a Ponderosa Pine Forest

Abstract: Ecological restoration treatments are widely applied in southwestern ponderosa pine forests to convert them to an open canopy structure similar to that found at the time of Euro-American settlement. An experiment was initiated in northern Arizona in 1994 to evaluate long-term ecosystem responses to 3 restoration treatments: 1) thinning from below (thinning), 2) thinning from below plus forest floor manipulation with periodic prescribed burning (composite), and 3) an untreated control. Results focus on total he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The only functional group that was affected by severity in 2008 was shrub cover, which was higher in sites that burned with low severity than high severity. It is not uncommon for forb, graminoid, and shrub cover to decrease one to three years post fire (Metlen et al 2004;Collins et al 2007;Knapp et al 2007;Dodson et al 2008); however, some studies have shown increases in understory vegetation cover (Armour et al 1984;Moore et al 2006;Ellsworth and Kauffman 2010). Metlen and Fiedler (2006) found that native plant cover was significantly lower initially post fire (same year as the prescribed burn) than unburned sites, however no differences were found in cover one to three years between burned sites and unburned sites in a ponderosa pine-Douglas-fir forest.…”
Section: Discussionmentioning
confidence: 99%
“…The only functional group that was affected by severity in 2008 was shrub cover, which was higher in sites that burned with low severity than high severity. It is not uncommon for forb, graminoid, and shrub cover to decrease one to three years post fire (Metlen et al 2004;Collins et al 2007;Knapp et al 2007;Dodson et al 2008); however, some studies have shown increases in understory vegetation cover (Armour et al 1984;Moore et al 2006;Ellsworth and Kauffman 2010). Metlen and Fiedler (2006) found that native plant cover was significantly lower initially post fire (same year as the prescribed burn) than unburned sites, however no differences were found in cover one to three years between burned sites and unburned sites in a ponderosa pine-Douglas-fir forest.…”
Section: Discussionmentioning
confidence: 99%